Source of household water as main risk factor of soil-transmitted helminth infections among elementary school pupils in Wamena District, Jayawijaya Regency, Papua - Semuel Sandy; Tri Nury Kridningsih (Faculty of Medicine, Universitas Trisakti, 2023)
BackgroundSoil-transmitted helminth (STH) infections are caused by three types of worms: Ascaris lumbricoides, Trichuris trichiura, and hookworms. Soil-transmitted helminth infections have significant health and socioeconomic implications for communities in developing countries, particularly in Indonesia. This study aims to determine the prevalence and risk factors of STH infections among elementary school pupils in Wamena District. MethodsThe study design used was a cross-sectional design involving 317 elementary school pupils. The children were interviewed using a structured questionnaire that included demographic information, hygiene, and environmental sanitation data of the respondents. Stool samples were collected from all consenting participants in sterile plastic containers and were analyzed within 24 hours of collection, using the Kato-Katz method. The data were analyzed using bivariate statistical analysis (Chi-square) and multivariate analysis (logistic regression). ResultsThe prevalence of helminthiasis among elementary school pupils was 19.9% (63/317). STH prevalence of mild category was 17.4% (55/317). The risk factors for STH infections among school children were the habit of not washing hands with soap after defecation, with an odds ratio of 5.04 [95% CI (2.22-11.48)], and the source of water for household use, with an odds ratio of 7.22 [95% CI (3.66-14.22)]. ConclusionThe prevalence of helminthiasis was found to be 19.9% (63/317), with an STH prevalence of mild category. Risk factors for STH infections included the habit of not washing hands with soap after defecation and the source of water for household use.